Increasing Student Motivation through the Use of Alternative Assessments in Basic Physics Online Lectures - Yusmaridi M (Indonesian Journal of Science and Education (IJOSE), 2021)
Poor student motivation in the online lecture process encourages researchers to provide a treatment that results in better student motivation in basic physics courses. Student learning motivation in the basic physics course is 30.38 with a poor category. The treatment applied in this study is to apply alternative assessments in the form of paper assessments, knowledge assessments, portfolio assessments, and discussion assessments. This study aims to determine how to increase learning motivation that occurs in students after the implementation of alternative assessments in online lectures. The research method used in this study is a pre-experimental method with one group pretest posttest design. The instrument used is a scale of student learning motivation attitudes using a Likert scale. Student learning motivation after the implementation of the alternative assessment has a value of 89.50 in the very good category. The increase in student learning motivation has increased significantly with a value of <N-Gain> of 0.85. Various assessments that are not only concerned with knowledge competencies can increase student motivation in carrying out basic physics online lectures.